A memristor-based system with hidden hyperchaotic attractors, its circuit design, synchronisation via integral sliding mode control and an application to voice encryption. (10th July 2019) - Vaidyanathan, Sundarapandian; Azar, Ahmad Taher; Akgul, Akif; Lien, Chang-Hua; Kacar, Sezgin; Cavusoglu, Unal
A memristor-based system with hyperchaos and hidden attractors is introduced in this research work. The proposed four-dimensional memristor-based system exhibits both line equilibrium and no-equilibrium for different choice of parameters. An experimental emulation of the memristor-based system is carried out by an electronic circuit. An adaptive integral sliding mode controller is designed for globally synchronising a pair of memristor-based hyperchaotic systems with unknown parameters. As another application, the memristive system with hyperchaos is applied for voice encryption, which has potential applications in cryptosystems, computing and secure communication.